Impact of anthropometric features on the applicability and accuracy of FibroScan® (M and XL) in overweight/obese patients. Issue 10 (26th September 2017) - Puigvehí, Marc; Broquetas, Teresa; Coll, Susanna; Garcia‐Retortillo, Montserrat; Cañete, Nuria; Fernández, Rosa; Gimeno, Javier; Sanchez, Juan; Bory, Felipe; Pedro‐Botet, Juan; Solà, Ricard; Carrión, José A
Abstract: Background and Aim: Transient elastography is the reference method for liver stiffness measurement (LSM) in the general population, having lower applicability in obese patients. We evaluated the applicability and diagnostic accuracy of the M and XL probes in overweight/obese patients to establish the most appropriate approach. Methods: From May 2013 to March 2015, we evaluated patients with a body mass index (BMI) ≥ 28 kg/m 2 . We constructed an algorithm with variables independently related to unreliable LSM with the M probe. Results: A total of 1084 patients were evaluated. M and XL probe applicability was 88.8% and 98%, respectively. Waist circumference (WC) (OR; 95% CI; P ) (0.97; 0.94–0.99; P  < 0.001) and skin‐capsule distance (SCD) (0.83; 0.79–0.87; P  < 0.001) were independently related to unreliable LSM (M probe). The SCD was > 25 mm in 5.5% of individuals with a BMI ≤ 35 kg/m 2 and a WC ≤ 117 cm, with LSM (M probe) applicability rising to 94.3%. In contrast, 36.9% of patients with a BMI > 35 kg/m 2 and/or a WC > 117 cm presented an SCD > 25 mm, with M probe applicability being 73.1%. The diagnostic accuracy (area under the receiver operator characteristic) using the M probe to identify significant steatosis (0.76), fibrosis (0.89), and cirrhosis (0.96) was very high in patients with a BMI ≤ 35 kg/m 2 and a WC ≤ 117 cm. Conclusions: The applicability and accuracy of the FibroScan ® M probe to identify fibrosis and steatosis was excellent in overweight and obesity grade I (BMI ≤ 35 kg/m 2 ) with a WC ≤ 117 cm. The XL probe increased the applicability of transient elastography in obesity grade II–III (BMI > 35 kg/m 2 ).